Cognitive-Behavioral Therapy for Generalized Anxiety Disorder is Associated with Attenuation of Limbic Activation to Threat-Related Facial Emotions - Fonzo, Gregory A. (2014)
BACKGROUND: The neural processes underlying the benefits of cognitive behavioral treatment (CBT) for generalized anxiety disorder (GAD) are not well understood. METHODS: Twenty-one (n=21) adults with a principal diagnosis of GAD and eleven (n=11) non-anxious healthy controls (HC) underwent functional magnetic resonance imaging while completing a facial emotion processing task. Responses to threat-related emotionality (i.e., the contrast of fear and angry vs. happy faces) were assessed at pretreatment and again following 10 sessions of CBT in the GAD group and a comparable waiting period in the HC group. RESULTS: At pretreatment, GAD participants displayed blunted responses in the amygdala, insula, and anterior cingulate to the happy face-processing comparison condition, and greater amygdalo-insular connectivity. CBT was associated with attenuated amygdalar and subgenual anterior cingulate activation to fear/angry faces and heightened insular responses to the happy face comparison condition, but had no apparent effects on connectivity. Pre-treatment abnormalities and treatment-related changes were not associated with symptoms of worry. LIMITATIONS: There was no active control condition (e.g., treatment waitlist) for comparison of treatment effects. CONCLUSIONS: Taken together, these results provide evidence for a dual-process psychotherapeutic model of neural systems changes in GAD in which cingulo-amygdalar reactivity to threat cues is attenuated while insular responses to positive facial emotions are potentiated. Future work is needed to determine the clinical implications of these changes and their specificity to CBT.